'In Every River, in Every Lake': Impacts of Beaver Population Change on Indigenous Livelihoods and Wellbeing in the Inuvialuit Settlement Region, Western Canadian Arctic - Callum Pearce; Melanie Rohse; Nicola Walshe; Helen C. Wheeler (Human Ecology, 2027)
Abstract Ecosystem transformation driven by climatic, environmental and societal factors poses interlinked ecological and social challenges for many Indigenous communities. For Inuvialuit communities in and around the lower Mackenzie Delta, in the western Canadian Arctic, recent changes in the population of beavers ( Castor canadensis ) have disrupted subsistence harvesting activities and travelling routes, exacerbating stresses linked to the cost of living and increasing the exposure of active harvesters to risk. Drawing on interviews with 25 Inuvialuit knowledge holders from the three communities of Inuvik, Tuktoyaktuk, and Aklavik, we investigated concerns around beaver population change in the western Arctic and the impact of this change on Inuvialuit livelihoods and wellbeing. Beyond the direct impact of beavers, the issues associated with ecosystem transformation pose challenges for Inuvialuit collective identity, the continuity of knowledge and connections to the land. While beaver population change was widely attributed to the local effects of a warming climate, participants also pointed to the effects of social transformations over recent decades. Ecological changes interact with social factors to produce complex and wide-ranging consequences for Indigenous communities.